Pentingnya Toleransi dan Kerukunan Antar Umat Beragama di Indonesia - Halide Hanum Koto; Iqbal Amar Muzaki; Afiyatun Kholifah (Universitas Majalengka, 2025)
Harmonious relations between adherents of different religions are still in the spotlight in this country of Indonesia. The diverse Indonesian nation has an important role in realizing a more peaceful and prosperous Indonesia. Tolerance in religion is a necessity that must be created for the sake of existing social stability. This article was written with the aim of describing the attitude of accepting differences in beliefs between religions in Indonesia, as well as providing an explanation of the index or value of tolerance for harmony between religious communities in Indonesia. This article was compiled using a literature study approach, namely a method of collecting data from books, articles, documents, and journals. The results obtained are that tolerance between diverse communities in Indonesia still needs to be improved. Although the index value shown from year to year is quite good, stability in implementing tolerance in Indonesia must continue to be maintained and improved. Because differences in religious beliefs should be mutually recognized, respected, and cooperate in goodness that is still within the corridor of each religion without damaging the beliefs of its adherents.